2003
DOI: 10.1152/jn.00765.2002
|View full text |Cite
|
Sign up to set email alerts
|

G Protein Signaling in a Neuronal Network is Necessary for Rhythmic Motor Pattern Production

Abstract: Clemens, Stefan, and Paul S. Katz. G protein signaling in a neuronal network is necessary for rhythmic motor pattern production. J Neurophysiol 89: 762-772, 2003; 10.1152/jn.00765.2002. G protein-coupled receptors are widely recognized as playing important roles in mediating the actions of extrinsic neuromodulatory inputs to motor networks. However, the potential for their direct involvement in rhythmic motor pattern generation has received considerably less attention. Results from this study indicate that G p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…10) is consistent with a presynaptic locus, because low-output synapses tend to facilitate more than high-output synapses (Zucker and Regehr, 2002). A presynaptic site of action is also consistent with previous results that showed DSI increasing neurotransmitter release from the other CPG neuron, C2 (Katz and Frost, 1995b;Clemens and Katz, 2003); however, these results do not rule out the possibility of changes in the sensitivity of the postsynaptic receptors in VFN. A similar change in sensitivity of AMPA receptors has been shown to play a role in modulating inspiratory drive to hypoglossal motor neurons (Bocchiaro et al, 2003).…”
Section: Presynaptic and Postsynaptic Mechanisms May Act As A Selectisupporting
confidence: 87%
“…10) is consistent with a presynaptic locus, because low-output synapses tend to facilitate more than high-output synapses (Zucker and Regehr, 2002). A presynaptic site of action is also consistent with previous results that showed DSI increasing neurotransmitter release from the other CPG neuron, C2 (Katz and Frost, 1995b;Clemens and Katz, 2003); however, these results do not rule out the possibility of changes in the sensitivity of the postsynaptic receptors in VFN. A similar change in sensitivity of AMPA receptors has been shown to play a role in modulating inspiratory drive to hypoglossal motor neurons (Bocchiaro et al, 2003).…”
Section: Presynaptic and Postsynaptic Mechanisms May Act As A Selectisupporting
confidence: 87%
“…It has been previously reported that DA causes a statistically significant increase in the peak amplitude of the PIR in DE-3, but not the area under the curve (Vallecorsa et al, 2007). An increase in overall cellular excitability is one way that neuromodulators can exert their influence over CPG activation (Clemens and Katz, 2003;Dai et al, 1998;Fedirchuk and Dai, 2004;Katz, 1998;Katz and Frost, 1997). Based on firing frequency, as an indicator of cell excitability, we found that DA reduced neuronal excitability, but only in the context of current injection.…”
Section: Pdis and Da Exert Distinct Effects On Specific Crawl-relatedmentioning
confidence: 75%
“…Further, activation of metabotropic receptors can lead to an augmentation of Ca 2ϩ -induced Ca 2ϩ release from internal stores. In lamprey reticulospinal axons, activation of metabotropic glutamate receptors leads to a rapid release of Ca 2ϩ from intracellular stores in a Ca 2ϩ -dependent manner (Cochilla and Alford 1998). These Ca 2ϩ signals would not be reproduced by the voltage signal alone in the absence of the synaptic inputs that triggered the second-messenger cascade that produced or augmented the Ca 2ϩ signals.…”
Section: Synaptic Inputs To C2 During the Smp Or Space-clamp Issues Mmentioning
confidence: 99%
“…The VSI result was somewhat unexpected; we hypothesized that neuromodulatory or synaptically driven Ca 2ϩ signals would contribute to the Ca 2ϩ signal recorded during the SMP. Dynamic biochemical signaling has been speculated to play a potentially integral role in the generation of the Tritonia SMP (Clemens and Katz 2003). Therefore we expected that VSI would receive at least some synaptic inputs during an SMP that would have produced some of the SMP Ca 2ϩ signal.…”
Section: Membrane Potential Excursions Can Fully Account For the Smp mentioning
confidence: 99%